2020
DOI: 10.3390/cancers12082072
|View full text |Cite
|
Sign up to set email alerts
|

Age Does Matter in Adolescents and Young Adults versus Older Adults with Advanced Melanoma; A National Cohort Study Comparing Tumor Characteristics, Treatment Pattern, Toxicity and Response

Abstract: Cutaneous melanoma is a common type of cancer in Adolescents and Young Adults (AYAs, 15–39 years of age). However, AYAs are underrepresented in clinical trials investigating new therapies and the outcomes from these therapies for AYAs are therefore unclear. Using prospectively collected nation-wide data from the Dutch Melanoma Treatment Registry (DMTR), we compared baseline characteristics, mutational profiles, treatment strategies, grade 3–4 adverse events (AEs), responses and outcomes in AYAs (n = 210) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Our data show that advanced melanoma in women more frequently harbors a BRAF V600E mutation, while melanoma in men more frequently has a NRAS or BRAF V600K mutation. Our data strengthen data from previously published smaller cohorts [ 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our data show that advanced melanoma in women more frequently harbors a BRAF V600E mutation, while melanoma in men more frequently has a NRAS or BRAF V600K mutation. Our data strengthen data from previously published smaller cohorts [ 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Younger patients may have a more active immune system which can lead to hepatitis or other IRAEs [ 32 ]. A recent study showed no increased rate of grade 3–4 side effects in general in younger patients compared to older adults [ 33 ]. However, for combination therapy-induced hepatitis it does seem a relevant risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Australia; 6 School of Public Health, The University of Queensland, Brisbane, Australia; 7 Queensland Melanoma Project (Princess Alexandra Hospital), The University of Queensland, Brisbane, Australia; and 8 Cancer Research UK Manchester and Faculty of Biology, Medicine and Health, University of Manchester, Manchester, UK Email: reza.ghiasvand@kreftregisteret.no…”
mentioning
confidence: 99%
“…Likewise, a recent cohort study found that baseline characteristics differed between young and old with advanced melanoma, but once treatment was initiated, tumour responses and melanoma-specific survival were similar. 6 Table 1 Risk of recurrence and association between sex, tumour characteristics and recurrence of primary melanoma, total and by age at diagnosis Total (n = 700)…”
mentioning
confidence: 99%
See 1 more Smart Citation